Self-adhesive polyether-ether-ketone-polyphenylene sulfone composite fiber and preparation method thereof

By using polyether ether ketone and polyphenylene sulfone to prepare self-adhesive composite fibers with a leather core structure, the adhesion difficulties and adhesive problems during the composite of acoustic films with aramid honeycombs are solved, and excellent mechanical properties and self-adhesive effects are achieved.

CN119531009AActive Publication Date: 2025-02-28DONGHUA UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411698601.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

In the prior art, the acoustic film prepared from polyether etherketone fibers cannot form a composite material by thermal bonding with aramid honeycombs, and the use of adhesives leads to poor interface adhesion and hole blocking problems.

Method used

Polyether ether ketone and polyphenylene sulfone are used to form self-adhesive composite fibers with a skin core structure, core layer and leather are prepared by a screw extrusion mechanism, and composite fibers with self-adhesiveness and excellent mechanical properties are formed by a secondary parallel drafting method.

Benefits of technology

The direct self-adhesion of the acoustic film and aramid honeycomb is realized, which improves the interface adhesion effect and mechanical properties, and avoids the use of adhesives and hole blocking problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119531009A_ABST
    Figure CN119531009A_ABST
Patent Text Reader

Abstract

The invention provides a self-adhesive polyether-ether-ketone-polyphenylene sulfone composite fiber and a preparation method thereof. The self-adhesive polyether-ether-ketone-polyphenylene sulfone composite fiber is of a skin-core structure, a core layer of the skin-core structure is polyether-ether-ketone, and a skin layer of the skin-core structure is polyphenylene sulfone. The self-adhesive polyether-ether-ketone-polyphenylene sulfone composite fiber disclosed by the invention is a composite fiber with a skin-core structure, and the self-adhesive polyether-ether-ketone-polyphenylene sulfone composite fiber has a self-adhesive property and an excellent mechanical property. The self-adhesive polyether-ether-ketone-polyphenylene sulfone composite fiber can be used for preparing an acoustic membrane, and due to the self-adhesiveness of the self-adhesive polyether-ether-ketone-polyphenylene sulfone composite fiber, when the self-adhesive polyether-ether-ketone-polyphenylene sulfone composite fiber is compounded with an aramid honeycomb, the acoustic membrane can be directly adhered to the aramid honeycomb to form a composite material, the interface adhesion effect is improved, and the interface bonding force is improved; the use of an adhesive is avoided, and the problem of hole blockage of the acoustic membrane caused by the adhesive is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber and a preparation method thereof. Background Art

[0002] Polyetheretherketone (PEEK) has excellent mechanical properties, high temperature resistance, corrosion resistance and other characteristics. It can be prepared into polyetheretherketone fiber by melt spinning, and then the polyetheretherketone fiber is prepared into an acoustic membrane by fiber polymerization. The acoustic membrane has good sound insulation, sound absorption, reflection and other functions, and is often used in the engine field. However, due to the high melting point of polyetheretherketone itself, the acoustic membrane prepared from polyetheretherketone fiber cannot be composited with aramid honeycomb by thermal bonding to form a composite material, which limits its application.

[0003] In order to composite the acoustic membrane made of polyetheretherketone fiber with aramid honeycomb, the prior art usually requires the use of an adhesive (such as an epoxy resin adhesive) to cure the acoustic membrane and the aramid honeycomb to prepare a composite material (Noise Reduction of honeycomb sandwich panels with acoustic mesh caps, Proc. Mtgs. Acoust., 2009, 8, 065002; Sound insulation performance of honeycombcore aluminum sandwich panels with flexible epoxy-based foam infill, Composite Structures, 2023, 319, 117149). In the composite material, the adhesion of the acoustic membrane made of polyetheretherketone fiber and the aramid honeycomb relies on the adhesive, the contact surface is small, and there is a poor interface adhesion effect, which leads to the problem of poor mechanical properties of the composite material; at the same time, the adhesive is a liquid solution before curing, which is easy to flow into the pores of the acoustic membrane, causing a pore blocking problem.

[0004] Therefore, obtaining a polyetheretherketone fiber that has both excellent mechanical properties and self-adhesiveness is a technical problem that needs to be solved urgently in the art. Summary of the invention

[0005] The invention provides a self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber. The self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber uses polyetheretherketone as a core layer and polyphenylene sulfone as a skin layer to form a composite fiber with a skin-core structure. The self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber has self-adhesiveness and excellent mechanical properties.

[0006] The present invention also provides a method for preparing a self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber, which can prepare a self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber with self-adhesiveness and excellent mechanical properties. The preparation method has a simple process and is suitable for wide promotion and application.

[0007] The present invention also provides an acoustic membrane, which is made of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber, so that the acoustic membrane has self-adhesiveness and excellent mechanical properties.

[0008] A first aspect of the present invention provides a self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber having a core-skin structure, wherein the core layer of the core-skin structure is polyetheretherketone and the skin layer is polyphenylene sulfone.

[0009] The self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber as described above has a melt index of 60 to 120 g / 10 min and a melt index of 20 to 80 g / 10 min.

[0010] In the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber as described above, the mass ratio of the polyetheretherketone to the polyphenylene sulfone is (1-3):1.

[0011] The second aspect of the present invention provides a method for preparing the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber, comprising:

[0012] The polyetheretherketone and the polyphenylene sulfone are dried respectively to obtain dried polyetheretherketone and dried polyphenylene sulfone;

[0013] Putting the dried polyetheretherketone into a first screw extruder to melt, and performing a first extrusion to obtain a core layer;

[0014] Putting the dried polyphenylene sulfone into a second screw extruder to melt, and performing a second extrusion to obtain a skin layer;

[0015] The core layer and the skin layer are weighed and squeezed into a skin-core spinning assembly according to a ratio for spinning treatment to obtain self-adhesive polyetheretherketone-polyphenylene sulfone primary fibers;

[0016] The self-adhesive polyetheretherketone-polyphenylene sulfone nascent fiber is subjected to a stretching-heat setting treatment by a two-stage parallel stretching method to obtain the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber with a skin-core structure.

[0017] In the method for preparing the self-adhesive polyetheretherketone-polyphenylenesulfone composite fiber, polyphenylenesulfone and polyetheretherketone are dried at 150° C. to 165° C. in a nitrogen atmosphere until the moisture content is less than 50 ppm.

[0018] In the method for preparing the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber as described above, the temperature of the first extrusion is 370° C. to 400° C. and the pressure is 6 MPa to 8 MPa.

[0019] In the method for preparing the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber as described above, the temperature of the second extrusion is 380° C. to 410° C. and the pressure is 6 MPa to 8 MPa.

[0020] In the method for preparing the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber as described above, the spinning treatment temperature is 370° C. to 400° C. and the spinning speed is 1200 m / min to 2000 m / min.

[0021] As described above, the preparation method of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber, during the stretching-heat setting treatment, the primary stretching temperature is 140°C to 160°C, the secondary stretching temperature is 210°C to 230°C, the stretching and winding speed is 750m / min to 850m / min, the stretching ratio is 1.5 times to 3.0 times, and the heat setting temperature is 240°C to 280°C.

[0022] The third aspect of the present invention provides an acoustic membrane, which is made of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber.

[0023] The self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber provided by the present invention is a composite fiber with a core-skin structure formed by using polyetheretherketone as a core layer and polyphenylene sulfone as a skin layer, and the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber has self-adhesiveness and excellent mechanical properties. The self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber of the present invention can be used to prepare an acoustic membrane. Due to its own self-adhesiveness, it can be directly adhered to an aramid honeycomb to form a composite material, which can improve the interfacial adhesion effect and the interfacial bonding force, so that the composite material also has excellent mechanical properties; and the use of adhesives is avoided, so as to avoid the problem of pore blocking of the acoustic membrane caused by adhesives. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 is a cross-sectional view of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber of Example 1 of the present invention, wherein a is polyphenylene sulfone, b is polyetheretherketone, and c is polyphenylene sulfone;

[0026] Figure 2 is a cross-sectional view of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber of Example 2 of the present invention, wherein a is polyphenylene sulfone, b is polyetheretherketone, and c is polyphenylene sulfone;

[0027] Figure 3 is a cross-sectional view of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber of Example 3 of the present invention, wherein a is polyphenylene sulfone, b is polyetheretherketone, and c is polyphenylene sulfone;

[0028] Figure 4 This is a cross-sectional view of the self-adhesive polyetheretherketone-polyphenylenesulfone composite fiber of Example 4 of the present invention, wherein a is polyphenylenesulfone and b is polyetheretherketone. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Unless otherwise specified, the raw materials and reagents used in the following examples can be obtained from commercial sources; the processes used, unless otherwise specified, are conventional processes in the art.

[0031] It should be noted that the descriptions involving “first”, “second”, etc. in the present invention are only for descriptive purposes and therefore cannot be understood as limiting the present invention.

[0032] The first aspect of the present invention provides a self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber having a core-skin structure, wherein the core layer of the core-skin structure is polyetheretherketone and the skin layer is polyphenylene sulfone.

[0033] In the present invention, the melting point of polyetheretherketone is 340°C.

[0034] In the present invention, the glass transition temperature of polyphenylene sulfone is 210°C to 225°C, and it can be melted at a temperature of 280°C to 320°C, and it has a high viscosity. The inventors have found through research that polyphenylene sulfone can be matched with polyetheretherketone to prepare a composite fiber with a skin-core structure (self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber); since the melting point of polyetheretherketone is 340°C, the composite fiber can be adhered with polyphenylene sulfone as a hot melt adhesive at a temperature less than 340°C.

[0035] The invention utilizes polyetheretherketone and polyphenylene sulfone to form a self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber with a skin-core structure, wherein polyetheretherketone is used as the core layer of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber, and polyphenylene sulfone is used as the skin layer of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber, and the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber has self-adhesiveness and excellent mechanical properties.

[0036] In a specific embodiment, the melt index of polyetheretherketone is 60 to 120 g / 10 min, and the melt index of polyphenylene sulfone is 20 to 80 g / 10 min.

[0037] When the melt index of polyetheretherketone and the melt index of polyphenylene sulfone are within the above range, polyphenylene sulfone and polyetheretherketone have spinnability, and self-adhesive polyetheretherketone-polyphenylene sulfone composite fibers with excellent self-adhesiveness and mechanical properties can be prepared by melt spinning.

[0038] For example, the melt index of polyetheretherketone may be any one of 60 g / 10 min, 70 g / 10 min, 80 g / 10 min, 90 g / 10 min, 100 g / 10 min and 120 g / 10 min, and a range consisting of any two thereof;

[0039] The melt index of polyphenylene sulfone may be any one of 20 g / 10 min, 30 g / 10 min, 40 g / 10 min, 50 g / 10 min, 60 g / 10 min, 70 g / 10 min and 80 g / 10 min, or a range consisting of any two of these.

[0040] In some embodiments, the melt index of polyetheretherketone may preferably be 80 g / 10 min, and the melt index of polyphenylene sulfone may preferably be 40 g / 10 min.

[0041] In a specific embodiment, the mass ratio of polyetheretherketone to polyphenylene sulfone is (1-3):1.

[0042] When the parameters of the mass ratio of polyetheretherketone to polyphenylene sulfone are within the above range, a self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber with excellent self-adhesiveness and mechanical properties can be prepared. The inventors have shown through a large number of studies that if the mass ratio of polyetheretherketone to polyphenylene sulfone is greater than 3:1, there are too many core layers, the uniformity of the distribution of the core layer and the skin layer decreases, the tensile strength decreases, and the mechanical properties deteriorate; if the mass ratio of polyetheretherketone to polyphenylene sulfone is less than 1:1, the mechanical properties of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber using polyphenylene sulfone as the main raw material will also deteriorate. This may be because polyphenylene sulfone is an amorphous material and cannot provide strong mechanical support. Therefore, the mechanical properties of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber prepared using polyphenylene sulfone as the main raw material decrease.

[0043] For example, the mass ratio of polyetheretherketone to polyphenylene sulfone may be any one of 1:1, 2:1 and 3:1, and a range consisting of any two of them.

[0044] In some embodiments, the mass ratio of polyetheretherketone to polyphenylene sulfone may preferably be 2:1.

[0045] The second aspect of the present invention provides a method for preparing a self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber, comprising:

[0046] The polyetheretherketone and the polyphenylene sulfone are dried respectively to obtain dried polyetheretherketone and dried polyphenylene sulfone;

[0047] Put the dried polyetheretherketone into a first screw extruder to melt, and perform a first extrusion to obtain a core layer;

[0048] Put the dried polyphenylene sulfone into a second screw extruder to melt, and then perform a second extrusion to obtain a skin layer;

[0049] The core layer and the skin layer are weighed and squeezed into the skin-core spinning assembly according to the ratio for spinning treatment to obtain self-adhesive polyetheretherketone-polyphenylene sulfone primary fibers;

[0050] The self-adhesive polyetheretherketone-polyphenylene sulfone nascent fibers are subjected to a drawing-heat setting treatment by a two-stage parallel drawing method to obtain a self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber with a skin-core structure.

[0051] The present invention does not particularly limit the specific forms of polyetheretherketone and polyphenylene sulfone, and they can be selected according to actual needs. In some embodiments, polyetheretherketone slices and polyphenylene sulfone slices can be selected.

[0052] The present invention does not specifically limit the instrument used for the above-mentioned measurement. In some embodiments, a metering pump can be selected for measurement.

[0053] The invention adopts the preparation method to prepare self-adhesive polyetheretherketone-polyphenylene sulfone composite fibers with self-adhesiveness and excellent mechanical properties. The preparation method has simple process and is suitable for wide promotion and application.

[0054] In a specific embodiment, polyphenylene sulfone and polyetheretherketone are dried at 150° C. to 165° C. in a nitrogen atmosphere to a moisture content of less than 50 ppm.

[0055] When polyphenylene sulfone and polyetheretherketone are dried to a moisture content of less than 50 ppm, the core layer and the skin layer prepared respectively have a low moisture content, which can prevent the formation of bubbles during the spinning process, induce the stress concentration of the spinning fluid and cause the occurrence of filament hair and filament breakage, which is beneficial to improving the mechanical properties of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber.

[0056] In a specific embodiment, the temperature of the first extrusion is 370° C. to 400° C. and the pressure is 6 MPa to 8 MPa.

[0057] When the parameters of the temperature and pressure of the first extrusion are within the above ranges, the molten polyetheretherketone can be completely filled in the screw of the first screw extruder, thereby preparing the core layer.

[0058] Exemplarily, the temperature of the first extrusion may be any one of 370° C., 380° C., 390° C. and 400° C., and a range consisting of any two thereof;

[0059] The pressure may be any one of 6 MPa, 7 MPa and 8 MPa, or a range consisting of any two of them.

[0060] In a specific embodiment, the temperature of the second extrusion is 380° C. to 410° C. and the pressure is 6 MPa to 8 MPa.

[0061] When the parameters of the temperature and pressure of the second extrusion are within the above ranges, the molten polyphenylene sulfone can completely fill the screw of the second screw extruder, thereby preparing the skin layer.

[0062] Exemplarily, the temperature of the first extrusion may be any one of 380° C., 390° C., 400° C. and 410° C., and a range consisting of any two thereof;

[0063] The pressure may be any one of 6 MPa, 7 MPa and 8 MPa, or a range consisting of any two of them.

[0064] In a specific embodiment, the spinning process has a temperature of 370° C. to 400° C. and a speed of 1200 m / min to 2000 m / min.

[0065] When the parameters of the temperature and speed of the spinning process are within the above range, the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber can be continuously prepared, and the prepared self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber maintains excellent mechanical properties. The inventors have found through research that when the temperature of the spinning process is lower than 370°C, the viscosity of the self-adhesive polyetheretherketone-polyphenylene sulfone nascent fiber increases sharply and cannot be extruded; when the temperature is higher than 400°C, the viscosity of the self-adhesive polyetheretherketone-polyphenylene sulfone nascent fiber decreases sharply, the spinnability of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber decreases, and it cannot be fiberized.

[0066] Exemplarily, the temperature of the spinning process may be any one of 370° C., 380° C., 390° C. and 400° C., and a range consisting of any two thereof;

[0067] The speed may be any one of 1200 m / min, 1300 m / min, 1400 m / min, 1500 m / min, 1600 m / min, 1700 m / min, 1800 m / min, 1900 m / min and 2000 m / min, or a range consisting of any two of them.

[0068] In a specific embodiment, during the stretching-heat setting treatment, the primary stretching temperature is 140°C to 160°C, the secondary stretching temperature is 210°C to 230°C, the stretching winding speed is 750m / min to 850m / min, the stretching ratio is 1.5 times to 3.0 times, and the heat setting temperature is 240°C to 280°C.

[0069] When the parameters of the primary drawing temperature, the secondary drawing temperature, the drawing and winding speed, the drawing ratio and the heat setting temperature are within the above range during the drawing-heat setting treatment, a self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber with self-adhesiveness and excellent mechanical properties can be prepared. The inventors analyzed this and believed that the reasons may be: (1) Polyetheretherketone is used as the mechanical support layer, and its glass transition temperature is 140°C. Therefore, when the primary drawing temperature is 140°C to 160°C, the orientation degree of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber is significantly improved, and it has excellent mechanical properties; (2) The glass transition temperature of polyphenylene sulfone is 210°C to 225°C. Therefore, when the secondary drawing temperature is 210°C to 230°C, the orientation degree of polyphenylene sulfone can be increased, thereby improving the self-adhesiveness of the polyetheretherketone-polyphenylene sulfone composite fiber. The mechanical properties of polyetheretherketone-polyphenylene sulfone composite fibers are as follows: (1) after primary drawing, the orientation degree of polyetheretherketone is relatively high, and it can crystallize at 210℃~230℃, forming a stable de-orientation and inhibiting the de-orientation of the molecular chain; (2) when the heat setting temperature is 240℃~280℃, the crystallization of polyetheretherketone is more perfect and the mechanical properties are further improved; (3) when the drawing ratio is 1.5 times~3.0 times, the drawing stability is high, and a self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber with self-adhesiveness and excellent mechanical properties can be prepared. In addition, the inventors have found through extensive research that: (1) when the primary drawing temperature is higher than 160°C, the polyetheretherketone molecular chain moves violently, is easily tangled during the drawing process, and has reduced mechanical properties; (2) when the drawing ratio is less than 1.5 times, the drawing tension of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber is low, and the drawing stability is reduced; when the drawing ratio is higher than 3.0 times, the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber is prone to drawing fracture, and has reduced mechanical properties.

[0070] The third aspect of the present invention provides an acoustic membrane, which is made of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber. The acoustic membrane has self-adhesiveness and excellent mechanical properties; and due to the self-adhesiveness of the acoustic membrane itself, it can be directly adhered to the aramid honeycomb to form a composite material, avoiding the use of adhesives.

[0071] The present invention is further described below through specific embodiments.

[0072] Example 1

[0073] In this embodiment, the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber is prepared by the following process:

[0074] The polyetheretherketone slices with a melt index of 80 g / 10 min and the polyphenylene sulfone slices with a melt index of 80 g / 10 min were respectively transferred to a hot air drying device, and dried at 165° C. in a nitrogen atmosphere for 6 hours to obtain dried polyetheretherketone slices and dried polyphenylene sulfone slices with a moisture content of less than 50 ppm;

[0075] Put the dried polyetheretherketone slices into a first screw extruder, melt them, and extrude them at a temperature of 375° C. and a pressure of 6 MPa to obtain a core layer;

[0076] The dried polyphenylene sulfone slices are placed in a second screw extruder, melted, and extruded at a temperature of 400° C. and a pressure of 6 MPa to obtain a skin layer;

[0077] The core layer and the skin layer are respectively weighed by a two-component core-skin spinning method, and then squeezed into a core-skin spinning assembly at a mass ratio of 2:1, and the spinning process is carried out at a temperature of 390°C and a speed of 1200m / min to obtain self-adhesive polyetheretherketone-polyphenylene sulfone primary fibers; a metering pump is used for metering;

[0078] The self-adhesive polyetheretherketone-polyphenylene sulfone nascent fibers were subjected to a stretching-heat setting treatment at a primary stretching temperature of 140°C, a secondary stretching temperature of 210°C, a stretching winding speed of 800 m / min, a stretching ratio of 2.0 times, and a heat setting temperature of 240°C to obtain the following: Figure 1 The self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber with a sheath-core structure is shown.

[0079] Depend on Figure 1 It can be seen that the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber has self-adhesiveness and a skin-core structure, the distribution of the skin layer and the core layer is unstable, and a large amount of polyphenylene sulfone enters the core layer, resulting in pulp penetration.

[0080] Example 2

[0081] In this embodiment, the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber is prepared by the following process:

[0082] The polyetheretherketone slices with a melt index of 120 g / 10 min and the polyphenylene sulfone slices with a melt index of 20 g / 10 min were respectively transferred to a hot air drying device, and dried at 160° C. in a nitrogen atmosphere for 6 hours to obtain dried polyetheretherketone slices and dried polyphenylene sulfone slices with a moisture content of less than 50 ppm;

[0083] Put the dried polyetheretherketone slices into a first screw extruder, melt them, and extrude them at a temperature of 390° C. and a pressure of 6 MPa to obtain a core layer;

[0084] The dried polyphenylene sulfone slices are placed in a second screw extruder, melted, and extruded at a temperature of 400° C. and a pressure of 6 MPa to obtain a skin layer;

[0085] The core layer and the skin layer are respectively weighed by a two-component core-skin spinning method, and then squeezed into a core-skin spinning assembly at a mass ratio of 2:1, and the spinning process is carried out at a temperature of 390°C and a speed of 1200m / min to obtain self-adhesive polyetheretherketone-polyphenylene sulfone primary fibers; a metering pump is used for metering;

[0086] The self-adhesive polyetheretherketone-polyphenylene sulfone nascent fibers were subjected to a stretching-heat setting treatment at a primary stretching temperature of 160°C, a secondary stretching temperature of 225°C, a stretching winding speed of 800 m / min, a stretching ratio of 2.1 times, and a heat setting temperature of 260°C to obtain the following: Figure 2 The self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber with a sheath-core structure is shown.

[0087] Depend on Figure 2 It can be seen that the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber has self-adhesiveness and a skin-core structure, and the distribution of the skin layer and the core layer is unstable. Part of the polyphenylene sulfone enters the core layer, resulting in pulp penetration.

[0088] Example 3

[0089] In this embodiment, the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber is prepared by the following process:

[0090] Transferring polyetheretherketone slices with a melt index of 120 g / 10 min and polyphenylene sulfone slices with a melt index of 80 g / 10 min to a hot air drying device, respectively, and drying them at 160° C. in a nitrogen atmosphere for 6 hours to obtain dried polyetheretherketone slices and dried polyphenylene sulfone slices with a moisture content of less than 50 ppm;

[0091] Put the dried polyetheretherketone slices into a first screw extruder, melt them, and extrude them at a temperature of 375° C. and a pressure of 6 MPa to obtain a core layer;

[0092] The dried polyphenylene sulfone slices are placed in a second screw extruder, melted, and extruded at a temperature of 390° C. and a pressure of 6 MPa to obtain a skin layer;

[0093] The core layer and the skin layer are respectively weighed by a two-component core-skin spinning method, and then squeezed into a core-skin spinning assembly at a mass ratio of 2:1, and the spinning process is carried out at a temperature of 385°C and a speed of 1200m / min to obtain self-adhesive polyetheretherketone-polyphenylene sulfone primary fibers; a metering pump is used for metering;

[0094] The self-adhesive polyetheretherketone-polyphenylene sulfone nascent fibers were subjected to a stretching-heat setting treatment at a primary stretching temperature of 160°C, a secondary stretching temperature of 225°C, a stretching winding speed of 800 m / min, a stretching ratio of 2.2 times, and a heat setting temperature of 260°C to obtain the following: Figure 3 The self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber with a sheath-core structure is shown.

[0095] Depend on Figure 3 It can be seen that the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber has self-adhesiveness and a skin-core structure, the skin layer and the core layer are distributed stably, and only a small part of the polyphenylene sulfone enters the core layer.

[0096] Example 4

[0097] In this embodiment, the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber is prepared by the following process:

[0098] The polyetheretherketone slices with a melt index of 80 g / 10 min and the polyphenylene sulfone slices with a melt index of 40 g / 10 min were respectively transferred to a hot air drying device, and dried at 160° C. in a nitrogen atmosphere for 6 hours to obtain dried polyetheretherketone slices and dried polyphenylene sulfone slices with a moisture content of less than 50 ppm;

[0099] Put the dried polyetheretherketone slices into a first screw extruder, melt them, and extrude them at a temperature of 390° C. and a pressure of 6 MPa to obtain a core layer;

[0100] The dried polyphenylene sulfone slices are placed in a second screw extruder, melted, and extruded at a temperature of 400° C. and a pressure of 6 MPa to obtain a skin layer;

[0101] The core layer and the skin layer are respectively weighed by a two-component core-skin spinning method, and then squeezed into a core-skin spinning assembly at a mass ratio of 2:1, and the spinning process is carried out at a temperature of 390°C and a speed of 1200m / min to obtain self-adhesive polyetheretherketone-polyphenylene sulfone primary fibers; a metering pump is used for metering;

[0102] The self-adhesive polyetheretherketone-polyphenylene sulfone nascent fibers were subjected to a stretching-heat setting treatment at a primary stretching temperature of 140°C, a secondary stretching temperature of 225°C, a stretching winding speed of 800 m / min, a stretching ratio of 2.5 times, and a heat setting temperature of 260°C to obtain the following: Figure 4 The self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber with a sheath-core structure is shown.

[0103] Depend on Figure 4It can be seen that the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber has self-adhesiveness and a skin-core structure, and the skin layer and the core layer are evenly distributed without pulp cross-linking.

[0104] Comparative Example 1

[0105] The preparation of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber provided in this comparative example is basically the same as that in Example 4, except that:

[0106] The melt index of polyetheretherketone chips is 50g / 10min.

[0107] Comparative Example 2

[0108] The preparation of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber provided in this comparative example is basically the same as that in Example 4, except that:

[0109] The melt index of polyetheretherketone chips is 130g / 10min.

[0110] Comparative Example 3

[0111] The preparation of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber provided in this comparative example is basically the same as that in Example 4, except that:

[0112] The melt index of the polyphenylene sulfone chips is 10 g / 10 min.

[0113] Comparative Example 4

[0114] The preparation of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber provided in this comparative example is basically the same as that in Example 4, except that:

[0115] The melt index of the polyphenylene sulfone chips was 90 g / 10 min.

[0116] Comparative Example 5

[0117] The preparation of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber provided in this comparative example is basically the same as that in Example 4, except that:

[0118] The core layer and the skin layer were weighed separately by a two-component skin-core spinning method and then extruded into a skin-core spinning assembly at a mass ratio of 0.8:1.

[0119] Comparative Example 6

[0120] The preparation of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber provided in this comparative example is basically the same as that in Example 4, except that:

[0121] The core layer and the skin layer are weighed separately by a two-component skin-core spinning method and then squeezed into a skin-core spinning assembly at a mass ratio of 4:1.

[0122] Comparative Example 7

[0123] Preparation of polyetheretherketone-polyphenylene sulfone composite fiber provided in this comparative example:

[0124] The polyetheretherketone slices with a melt index of 80 g / 10 min and the polyphenylene sulfone slices with a melt index of 40 g / 10 min were respectively transferred to a hot air drying device, and dried at 160° C. in a nitrogen atmosphere for 6 hours to obtain dried polyetheretherketone slices and dried polyphenylene sulfone slices with a moisture content of less than 50 ppm;

[0125] The dried polyetheretherketone slices and the dried polyphenylene sulfone slices are weighed and put into a screw extruder at a mass ratio of 2:1 for melting, and extruded at a temperature of 390°C and a pressure of 6 MPa to obtain a melt; a metering pump is used for metering;

[0126] The melt is extruded into a sheath-core spinning assembly, and a spinning process is performed at a temperature of 390° C. and a speed of 1200 m / min to obtain polyetheretherketone-polyphenylene sulfone primary fibers;

[0127] A two-stage parallel drawing method was adopted, with the first-stage drawing temperature being 140°C, the second-stage drawing temperature being 225°C, the drawing winding speed being 800m / min, the drawing ratio being 2.5 times, and the heat setting temperature being 260°C, to carry out a drawing-heat setting treatment on the self-adhesive polyetheretherketone-polyphenylenesulfone nascent fiber to obtain a polyetheretherketone-polyphenylenesulfone composite fiber.

[0128] Performance Characterization

[0129] The following performance tests were performed on the self-adhesive polyetheretherketone-polyphenylene sulfone composite fibers of Examples 1-4 and Comparative Examples 1-7, and the test results are shown in Table 1;

[0130] (1) Tensile strength (cN / dtex): Tested in accordance with GB / T 14344-2022 “Chemical Fibers: Test Method for Tensile Properties of Filaments”;

[0131] (2) Denier (dtex): Tested in accordance with GB / T 14343-2008 “Chemical Fibers: Test Method for Linear Density of Filament”;

[0132] (3) Thermal shrinkage (%): Tested in accordance with GB / T 6505-2008 “Chemical fibers: Test method for thermal shrinkage of filaments”.

[0133] Table 1 Test results

[0134] project Spinnability Tensile strength (cN / dtex) Denier(dtex) Thermal shrinkage (%) Example 1 Can spin 3.8 16.3 5.53 Example 2 Can spin 4.1 15.5 4.94 Example 3 Can spin 4.3 14.8 4.77 Example 4 Can spin 5.3 13.0 3.24 Comparative Example 1 Unable to spin —— —— —— Comparative Example 2 Unable to spin —— —— —— Comparative Example 3 Unable to spin —— —— —— Comparative Example 4 Can spin 3.2 17.2 6.54 Comparative Example 5 Can spin 3.7 13.0 4.74 Comparative Example 6 Can spin 3.7 13.0 3.98 Comparative Example 7 Can spin 2.54 13.0 11.3

[0135] Analyze the data in the above table:

[0136] It can be seen from Examples 1 to 4 that the tensile strength of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber can reach up to 5.3 cN / dtex, which indicates that the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber prepared in the examples of the present invention has excellent mechanical properties.

[0137] By comparing Comparative Examples 1-2 with Example 4, it can be seen that when the melt index of the polyetheretherketone slice is 50g / 10min, spinning is impossible. This may be because the melt index of the polyetheretherketone slice is too low and its viscosity is too high, which will cause the melted polyetheretherketone to break during extrusion and cannot be spun; when the melt index of the polyetheretherketone slice is 130g / 10min, spinning is impossible. This may be because the viscosity of the polyetheretherketone is too low, and the prepared core layer cannot be filled in the sheath-core spinning assembly, resulting in significant hair breakage and spinning.

[0138] By comparing Comparative Examples 3-4 with Example 4, it can be seen that when the melt index of the polyphenylene sulfone slice is 10g / 10min, spinning is impossible. This may be because the melt index of the polyphenylene sulfone slice is too low and its viscosity is too high, which will cause serious breakage of the molten polyphenylene sulfone during extrusion, and obvious hair breakage will occur during the spinning process, making it impossible to use; when the melt index of the polyphenylene sulfone slice is 90g / 10min, the mechanical properties of the prepared self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber are reduced. This may be because the viscosity of the polyphenylene sulfone is too low, part of the prepared cortex is not filled, and the pulp phenomenon occurs, resulting in the reduction of the mechanical properties of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber.

[0139] By comparing Comparative Examples 5-6 with Example 4, it can be seen that when the mass ratio of the core layer and the skin layer is 0.8:1, the mechanical properties of the prepared self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber decrease. It is speculated that this may be because the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber uses polyphenylene sulfone as the main raw material, and polyphenylene sulfone is an amorphous material and cannot provide strong mechanical support. Therefore, the mechanical properties of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber decrease; when the mass ratio of the core layer and the skin layer is 4:1, the mechanical properties of the prepared self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber decrease. It is speculated that this may be because there are too many core layers in the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber, the uniformity of the distribution of the core layer and the skin layer decreases, the tensile strength decreases, and the mechanical properties of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber deteriorate.

[0140] By comparing Comparative Example 7 with Example 4, it can be seen that the polyetheretherketone-polyphenylene sulfone composite fiber prepared in Comparative Example 7 has no self-adhesiveness and its mechanical properties are significantly reduced. This may be because the compatibility of polyetheretherketone and polyphenylene sulfone is poor. Polyphenylene sulfone is a material heterogeneity, which easily causes fiber stress concentration, resulting in a significant decrease in the mechanical properties of the prepared polyetheretherketone-polyphenylene sulfone composite fiber. In addition, since the cortex of the polyetheretherketone-polyphenylene sulfone composite fiber is a mixture of polyetheretherketone and polyphenylene sulfone, the polyetheretherketone-polyphenylene sulfone composite fiber cannot melt at 320°C, and therefore cannot be used as a self-adhesive composite fiber; and when the melting temperature is increased to 340°C, the polyetheretherketone in the polyetheretherketone-polyphenylene sulfone composite fiber will melt, and the polyetheretherketone-polyphenylene sulfone composite fiber will mechanically disintegrate and cannot remain in a fibrous state.

[0141] In summary, the skin layer and the core layer of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber prepared in Example 4 are evenly distributed, have excellent mechanical properties (tensile strength higher than 5.2 cN / dtex), and can be applied to high-density woven fabrics (tensile strength greater than 5.0 cN / dtex). In addition, after the skin layer of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber is melted at high temperature, the core layer can still maintain excellent mechanical properties.

[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber, characterized in that: The invention has a skin-core structure, wherein the core layer of the skin-core structure is polyetheretherketone, and the skin layer is polyphenylene sulfone.

2. The self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber according to claim 1, characterized in that: The melting index of the polyetheretherketone is 60 to 120 g / 10 min, and the melting index of the polyphenylene sulfone is 20 to 80 g / 10 min.

3. The self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber according to claim 1, characterized in that: The mass ratio of the polyetheretherketone to the polyphenylene sulfone is (1-3):

1.

4. A method for preparing the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber according to any one of claims 1 to 3, characterized in that: include: The polyetheretherketone and the polyphenylene sulfone are dried respectively to obtain dried polyetheretherketone and dried polyphenylene sulfone; Putting the dried polyetheretherketone into a first screw extruder to melt, and performing a first extrusion to obtain a core layer; Putting the dried polyphenylene sulfone into a second screw extruder to melt, and performing a second extrusion to obtain a skin layer; The core layer and the skin layer are weighed and squeezed into a skin-core spinning assembly according to a ratio for spinning treatment to obtain self-adhesive polyetheretherketone-polyphenylene sulfone primary fibers; The self-adhesive polyetheretherketone-polyphenylene sulfone nascent fiber is subjected to a stretching-heat setting treatment by a two-stage parallel stretching method to obtain the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber with a skin-core structure.

5. The method for preparing the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber according to claim 4, characterized in that: The polyphenylene sulfone and polyetheretherketone were dried at 150° C. to 165° C. in a nitrogen atmosphere until the water content was less than 50 ppm.

6. The method for preparing the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber according to claim 4, characterized in that: The temperature of the first extrusion is 370° C. to 400° C., and the pressure is 6 MPa to 8 MPa.

7. The method for preparing the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber according to claim 4, characterized in that: The temperature of the second extrusion is 380° C. to 410° C., and the pressure is 6 MPa to 8 MPa.

8. The method for preparing the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber according to claim 4, characterized in that: The spinning process has a temperature of 370° C. to 400° C. and a speed of 1200 m / min to 2000 m / min.

9. The method for preparing the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber according to claim 4, characterized in that: During the stretching-heat setting treatment, the primary stretching temperature is 140°C to 160°C, the secondary stretching temperature is 210°C to 230°C, the stretching winding speed is 750m / min to 850m / min, the stretching ratio is 1.5 times to 3.0 times, and the heat setting temperature is 240°C to 280°C.

10. An acoustic membrane, characterized in that: The acoustic membrane is made of the self-adhesive polyetheretherketone-polyphenylene sulfone composite fiber according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Polyetheretherketone-base composite electromagnetic shielding material and preparation method thereof

    CN102321338A

  • Heat-bondable sheath-core composite fiber

    JP2023028056A

  • High-flow polyphenylsulfone compositions

    US20190127581A1